The new development economics after the Washington Consensus (New Delhi Tulika Books ; London Zed Books, 2006)
This volume provides an original and thought-provoking critique of the post-Washington Concensus in neoliberal economics. Aimed at academics and postgraduates, and policy-makers, in development economics, the text clearly presents current trends in th eory and policy within mainstream development economics.
Introduction: The economics of development and the development of economics ; The new development economics / Ben Fine -- From Washington to post-Washington consensus: illusions of development / Elisa Van Waeyenberge -- Kicking away the logic: f ree trade is neither the question nor the answer for development / Sonali Deraniyagala, Ben Fine -- New growth theory: more problem than solution ; Financial programming and the IMF ; The developmental state and the political economy of development / Ben Fine -- Analysis of technology and development: a critical review / Sonali Deraniyagala -- Privatization theory and practice: a critical analysis of policy evolution in the development context / Kate Bayliss -- From Washington to post-Washington consensus: the triumph of human capital / John Harriss -- Corruption and governance / Mushtaq Husain Khan -- Agriculture and development: towards a critique of the 'new neoclassical development economics' and of 'neoclassical neo-populism' / Terrence J. Byres -- Development and geography: current debates in historical perspective / Hugh Goodacre -- Pioneers of economic history / Dimitris Milonakis.
Includes bibliographical references and index.
Keywords: Development economics; Economic development; Economic development -- Political aspects; Economic development -- Technological innovations; Entwicklungsèokonomie.; Aufsatzsammlung